Metabolismo do ferro em hamsters infectados experimentalmente com leptospira interrogans sorovar pomona: influência na patogênese da doença - Sobroza, Ânderson Oliveira (2013)
Anemia in Leptospira interrogans infected individuals is one of the most common complications found in the severe form of the disease. Iron plays an important role in the hematopoietic processes; however, its precise metabolism on individuals with leptospirosis is still unknown. Therefore, the aim of this study was to analyze the classic iron markers associated to the storage process in hamsters experimentally infected by L. interrogans serovar Pomona (virulent strain LPF). Four groups with six hamsters each were used; two groups were controls (C7 and C14) and two were experimental groups with infected animals (T7 and T14). Blood samples were collected on the seventh (C7 and T7) and fourteenth days (C14 and T14) post-inoculation (PI). Iron availability was determined in sera samples by the assessment of iron, ferritin, transferrin, and iron binding capacity, whereas the bone marrow was also evaluated for the deposition of this metal by Pearl s reaction. Additionally, the total antioxidant capacity (TAC) and total oxidant status (TOS) were assessed, along with hepcidin and IL-6 levels to be involved in iron metabolism. Based on the results, it was possible to observe the onset of an acute condition with crisis hemolytic and regenerative response. The other parameters showed an increase in seric iron, ferritin, as well as a positive Pearl s reaction in animals from the groups T7 and T14 compared with the control groups. Transferrin levels decreased in animals from the group T14 with saturation index, but without statistical difference among all tested groups. TAC was increased in both periods, while TOS was increased only on day 14 PI. Hepcidin and IL-6 were statistically increased on days 7 and 14 PI. Therefore, it was observed that the serum profile from infected animals showed a strong hemolytic pattern, with some demonstration of ferric tissue sequestration. The results show that iron metabolism is activated in hamsters infected by L. interrogans sorovar Pomona, and therefore has participation in the pathogenesis of the disease.